2017
DOI: 10.1504/ijes.2017.081720
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trigonometric functions-based watermarking on blood vessel extraction: an application in ophthalmology imaging

Abstract: With the growth of globalisation, security has been a major concern in digital exchange of medical information. Data hiding, also referred as watermarking, was introduced to authenticate medical data which is sent over the network. Watermarking of electronic patient reports (EPR) for telemedicine demands robust, imperceptible, high payload techniques. Blood vessel extraction is mainly used for diabetic retinopathy (DR) for automatic extraction and classification of severity of diseases. In our current work, bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…In the previous works regarding the SGO algorithm, a value of 0.2 for the parameter c [29,30] was suggested, but, here, a trial and error procedure was performed and the value that offered the best convergence rate along with the optimized result was found to be 0.5. The experimental study also confirmed that the proposed SGO algorithm offered better execution time compared to other well-known heuristic algorithms such as PSO [52], FA [42,47] and BA [41] based thresholding procedures. Examples of the used RGB images are presented in Figure 3 along with the corresponding histogram of the three channels (i.e., R, G and B components) and the associated ground truth.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…In the previous works regarding the SGO algorithm, a value of 0.2 for the parameter c [29,30] was suggested, but, here, a trial and error procedure was performed and the value that offered the best convergence rate along with the optimized result was found to be 0.5. The experimental study also confirmed that the proposed SGO algorithm offered better execution time compared to other well-known heuristic algorithms such as PSO [52], FA [42,47] and BA [41] based thresholding procedures. Examples of the used RGB images are presented in Figure 3 along with the corresponding histogram of the three channels (i.e., R, G and B components) and the associated ground truth.…”
Section: Resultssupporting
confidence: 66%
“…where R a and R b are random numbers having the range [0,1] and X r,j is the knowledge (position) value of the chosen individual. From Equations (2) and 3, it can be observed that the implementation of the SGO algorithm is simple compared to other algorithms existing in the image processing domain [40][41][42][43][44][45][46][47][48]. The steps of the standard SGO algorithm can be described as in Algorithm 1.…”
Section: Social Group Optimizationmentioning
confidence: 99%
“…The authors indicate that they used the green channel of the original image to generate the watermark, and the other channels (red and blue) were used to embed the watermark. In [12], Dey et al presented a watermarking method applied to fundus images to insert an EPR into the blood vessels extracted using K-means segmentation. Additionally, the authors evaluated and found a percentage difference in accuracy (0.25%) in blood vessel extraction before and after watermarking.…”
Section: Watermarking Algorithmsmentioning
confidence: 99%
“…[9] presents an imperceptible watermark method for medical images and the authors include tests demonstrating that it does not affect computer vision-based automated diagnosis of retinal diseases. On the other hand, Dey et al [12] reported a watermarking algorithm for fundus images by inserting patient information, and evaluated that the embedding watermark process slightly modifies the blood vessel extraction.…”
mentioning
confidence: 99%
See 1 more Smart Citation